Analisis Perubahan Kualitas Udara di Kawasan PLTU Teluk Sirih Kota Padang Menggunakan Remote Sensing - Yulianita, Yulianita; Suryani, Novelisa; Mariati, Heny (Jurnal Pembangunan Nagari; Vol 7 No 2 (2022)DO - 10.30559/jpn.v7i2.315, 2022)
One of the impacts of PLTU development is air pollution. The study aims to analyze the average and identify changes in air quality in 2013 (before the power plant operates) and 2020 (after the power plant operates) in Bungus Teluk Kabung District  by  descriptive quantitative.analysis .  Changes in air quality were analyzed by  Landsat 8 satellite images in 2013 and 2020 with parameters were PM 10 , SO 2 and NO x .The average value of the parameter is calculated based on the air quality algorithm, and to measure changes in air quality standards apply ISPU. The results showed an average improvement in all air quality parameters. Based on the ISPU distribution of PM 10 values increased by 1 μg/m³, in 2013 the average value (1.9 μg/m³), in 2020 it became (2.9 μg/m³), included in the good category. SO 2 values in the medium category with an increase of 0.7 ρρm, in 2013 (63.3 ρρm) and in 2020 (64 ρρm). NO x is in the unhealthy category with an increase of 0.1 μg/m³, in 2013 (173.5 μg/m³) and in 2020 (173.6 μg/m³). The results of the wilcoxon difference test showed that all air quality parameters had a significant value of < 0.05, meaning that there was a significant difference in air quality before and after the power plant was built. The PLTU is expected to immediately minimize the smoke produced by burning coal using Clean Coal Technology.